Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Media Visual Pada Pembelajaran Seni Tari Di SMA Negeri 1 Padang Ganting - Rezi Ulfa Afriwen; Yuliasma Yuliasma (SENDRATASIK UNP, 2021)
This study aims to describe the use of visual media in dance learning in order to improve learning outcomes at SMAN 1 Padang Ganting. This type of research is class action research (PTK). The research implementation consists of 2 cycles with the stage of planning activities, implementation, observation and reflection. The data types in this study are primary data and secondary data. Data collection techniques are done by observation, interviews, documentation and tests. Data analysis techniques use a percentage formula. The results showed that visual media in the form of PowerPoint could improve student learning outcomes in dance art defence at SMA Negeri 1 Padang Ganting in class X IIS. 2 which is seen from the research process during the process of learning the art of dance. With the media it can also attract students 'attention and reduce the level of students ' saturation in the teaching and learning process. Visual Media in the form of PowerPoint can improve student dance learning outcomes, it is in the prove with the results of research with the average cognitive value gained in Cycle 1 with the acquisition of 78.5 while on cycle II with the acquisition of 89.5. Thus, visual media can improve student learning outcomes at SMAN 1 Padang Ganting.